Learning effectiveness in ERP systems training: a structural equation model of self-efficacy, passion, and resilience in higher education - Wei, Ran; Cao, Dongyue (Frontiers in Education, 2025)
The present study investigates the participation of 235 students from the Department of Supply Chain and Information Management at a university in Hong Kong in four training workshops focused on Enterprise Resource Planning (ERP) Systems. After each workshop, relevant questionnaire surveys were administered to gather data on students’ learning experiences and key variables, including self-efficacy, learning efficacy, passion, and resilience. The collected data were analyzed using structural equation modeling (SEM) to explore the interrelationships among these variables within the context of ERP systems training. The findings indicate that after completing a series of four ERP systems training workshops, participants with a bachelor’s degree and those receiving compensation demonstrated significant improvements in these four dimensions. These results underscore the pivotal role of self-efficacy as a motivational driver for learning and highlight the interplay between intrinsic motivation and external rewards in fostering passion for learning. Furthermore, the study reveals the dynamic nature of the relationship between passion and learning efficacy. In the initial stages of training, students exhibited high levels of engagement fueled by curiosity about the ERP systems. However, as task complexity increased, participants encountered greater challenges, which potentially diminished their enthusiasm and engagement. While external incentives, such as financial compensation, are traditionally considered effective motivators, this study found that the negative path coefficient associated with external rewards did not reach statistical significance. This suggests that the design of educational interventions should carefully balance internal and external motivational factors to maximize the effectiveness of ERP systems training. Moreover, this study provides valuable insights into the interrelationships among self-efficacy, learning efficacy, passion, and resilience within the context of ERP systems training. It also offers theoretical guidance for the development of future educational practices aimed at enhancing learning outcomes in ERP systems. This study is limited by the use of self-report measures and its focus on a single institutional context. Future research should broaden the sample and integrate objective performance metrics.